Synthesis of 1,2′-Biazulenes by Palladium-Catalyzed Unusual Homocoupling Reaction of 1-Haloazulenes in the Presence of Ferrocene - Shoji, Taku; Miyashita, Kanami; Araki, Takanori; Tanaka, Miwa; Maruyama, Akifumi; Sekiguchi, Ryuta; Ito, Shunji; Okujima, Tetsuo (Synthesis, 2016)
The synthesis of 1,2′-biazulenes was established by palladium-catalyzed homocoupling reactions of the corresponding 1-haloazulenes in the presence of ferrocene. The optical properties of the novel 1,2′-biazulenes were investigated by UV/Vis spectroscopy and theoretical calculations. The redox behaviors of 1,2′-biazulenes were also examined by cyclic voltammetry (CV) and differential pulse voltammetry (DPV).
Keywords: azulene; 1,2′-biazulene; homocoupling; UV/Vis spectrum; cyclic voltammetry